The Effectiveness of OECD Guidelines in Curbing Tax Avoidance through Transfer Pricing - Pires, Maria Fernanda (MZ Journal of Artificial Intelligence, 2024)
The increasing globalization of business operations has heightened concerns about tax avoidance strategies employed by multinational enterprises (MNEs). One significant area of concern is transfer pricing, which involves the pricing of transactions between related entities within a multinational group. This research paper examines the effectiveness of the Organization for Economic Co-operation and Development (OECD) Guidelines in addressing tax avoidance through transfer pricing. By analyzing the principles and recommendations set forth in the OECD's framework, this paper assesses their impact on tax compliance, international cooperation, and the overall reduction of tax avoidance. The findings indicate that while the OECD Guidelines have made significant strides in enhancing transparency and aligning tax practices with economic activities, challenges remain in their implementation and enforcement, particularly among developing countries.